Review of the book "Dialogue, argumentation and education: History, theory and practice", by Baruch B.Schwarz & Michael J.Baker - Perret-Clermont, Anne-Nelly (My University, 2018)
Perret-Clermont, A.-N. (2018). . J, 7(1), 101-107. doi: